حمــــــامـــات هادريــــــان Hadrian Baths بمدينة لبدة الكبرى (Comprehensive Journal of Science, 2025)
This research examines Hadrian's Baths in Leptis Magna, one of the most prominent architectural structures dating back to the Roman era, built during the reign of Emperor Hadrian in the second century AD. The research aims to highlight the architectural and engineering characteristics of these baths, analyze their various components and functions, and shed light on their role in the daily, social, health, and cultural life of the city's inhabitants.The study employs a descriptive-analytical approach, examining archaeological remains and data related to the baths, focusing on their architectural elements such as the hot and cold chambers, the heating system (hypocoust), and the water supply and drainage networks. The research also explores the social and cultural functions of this facility, considering it as a center for social interaction in addition to its role as a health center.The research concludes that Hadrian's Baths represent an advanced model of Roman architecture in terms of planning and engineering precision, reflecting a high level of urban organization and technological development. The findings also demonstrate that these baths played a significant role in enhancing the social and cultural life within Leptis Magna. The research concludes by emphasizing the importance of preserving this archaeological landmark, and the need to conduct more specialized studies that contribute to documenting and understanding the Roman architectural heritage in Libya.
Keywords: Hadrian – cold – hot – lukewarm – perspiration – toilets